CLASSIC BOOK SHELF OF EUGENIO CORTY: IN THE WORKSHOP OF THE NOVEL “CATONE ANTICO” - ROMANO, Dario (Accents and Paradoxes of Modern Philology, 2021)
On the 100th anniversary of Eugenio Corti’s birth (1921-2014), the article reports on the first study conducted on the material that the Italian author used to draft his historical novel Catone l'antico (Ares, Milan 2005). This is the third element of a trilogy defined by Corti himself as “racconti per immagini” (stories in images), since he has adopted a new literary style, very close to the languages of cinema, television and computers.The essay examines the genesis of the novel in order to understand how a modern writer tackles the times of an ever-evolving artistic production and it also determines any debts and credits of his creative work.Along a survey of Catone's preparatory material (whose summary is at the end of the article), it is possible to outline the main directions of Corti's research as well as to analyse the work from different perspectives, even to connect it to the rest of the author’s production.All things considered, the study proves that Eugenio Corti does not change his writing purposes, as his literary topics do. Through the life of a Roman man (ancient only for historical distance), the author of Il cavallo rosso (The Red Horse) continues to demonstrate how it is false the idea of freedom to live happy and free without man's wickedness. That was also an idea of the Communists, who have always censored the writer, through part of the leading and intellectual class of Italy.